2013
DOI: 10.1021/cs4003113
|View full text |Cite
|
Sign up to set email alerts
|

Facile Route for Synthesizing Ordered Mesoporous Ni–Ce–Al Oxide Materials and Their Catalytic Performance for Methane Dry Reforming to Hydrogen and Syngas

Abstract: A series of ordered mesoporous Ni–Ce–Al composite oxides with various cerium contents were synthesized via a one-pot route: evaporation-induced self-assembly (EISA) strategy and tested in methane dry reforming for hydrogen and synthesis gas production. Using this method, the hydrophobic nickel precursor was directly incorporated into the hydrophobic cores of surfactant micelles, and thus, the highly dispersed Ni nanoparticles were stabilized inside the mesopore channels of an alumina matrix. For comparison, Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
203
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(214 citation statements)
references
References 65 publications
9
203
2
Order By: Relevance
“…Comparable stability effects were recently claimed in the case of "one-pot" synthesized oxide-based catalysts tested in DRM [43,45,51,52,61] or in SRM [46], but such types of materials were never considered yet in the combined CSDRM reaction that involves much more drastic conditions (especially steam and high temperatures). Moreover, the present method introducing the active phase (Ni) and the structuring agent (P123 Pluronic triblock copolymer) in a same synthesis batch was, to our knowledge, never considered regarding nickel-alumina based mesoporous catalysts.…”
Section: Combined Factors Ensuring Catalytic Stability In Csdrmmentioning
confidence: 93%
“…Comparable stability effects were recently claimed in the case of "one-pot" synthesized oxide-based catalysts tested in DRM [43,45,51,52,61] or in SRM [46], but such types of materials were never considered yet in the combined CSDRM reaction that involves much more drastic conditions (especially steam and high temperatures). Moreover, the present method introducing the active phase (Ni) and the structuring agent (P123 Pluronic triblock copolymer) in a same synthesis batch was, to our knowledge, never considered regarding nickel-alumina based mesoporous catalysts.…”
Section: Combined Factors Ensuring Catalytic Stability In Csdrmmentioning
confidence: 93%
“…The patterns for all the shown meso-xLaNiAl samples exhibit mainly two wide diffraction peaks, which are corresponding to amorphous Al 2 O 3 [29]. No peaks associated with nickel species are found, indicating the high dispersion of Ni species inside the framework of the materials due to the advantages of the one-pot method [54]. Moreover, no La 2 O 3 characteristic peaks are observed for meso-xLaNiAl catalysts, indicating lanthanum species are either amorphous or well dispersed.…”
Section: Characterization Of Calcined Catalystsmentioning
confidence: 94%
“…Bobin et al [41] have shown that the amount of the active carbon pool which participates in dry reforming over supported Ni and Ni-Ru was very small. Dry reforming of methane over Ce 1−x−y M 1 x M 2 y O 2 -supported Ni catalysts (M 1 and M 2 are rare earth metals) with supports possessing high OSC (mol O g −1 ) was reported [10,[14][15][16][17]42,43]. The high activity of these catalytic systems was related with the participation of support's oxygen vacancies towards dissociation of CO 2 .…”
Section: Catalytic Performance Of Nimentioning
confidence: 99%